2007
DOI: 10.2174/157340507779940327
|View full text |Cite
|
Sign up to set email alerts
|

Small Animal Computed Tomography Imaging

Abstract: Micro Computed Tomography (micro-CT) was suggested in biomedical research to investigate tissues and small animals. Its use to characterize bone structures, vessels (e.g. tumor vascularization), tumors and soft tissues such as lung parenchyma has been shown. When co-registered, micro-CT can add structural information to other small animal imaging modalities. However, due to fundamental CT principles, high-resolution imaging with micro-CT demands for high x-ray doses and long scan times to generate a sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 68 publications
(143 reference statements)
2
47
0
1
Order By: Relevance
“…Using these settings, we demonstrated that the resolution achieved by VCT was sufficient to identify alterations of the lung texture and the larger airways in 3-day-old neonatal mice with a body weight of ,2-3 g. The maximum cumulative dose of 10 subsequent VCT scans was ,230 mGy [23], which was well tolerated by mice in our study and previous studies [36,37], thus allowing noninvasive longitudinal monitoring of lung disease in mice from neonatal to adult ages.…”
Section: Discussionmentioning
confidence: 54%
“…Using these settings, we demonstrated that the resolution achieved by VCT was sufficient to identify alterations of the lung texture and the larger airways in 3-day-old neonatal mice with a body weight of ,2-3 g. The maximum cumulative dose of 10 subsequent VCT scans was ,230 mGy [23], which was well tolerated by mice in our study and previous studies [36,37], thus allowing noninvasive longitudinal monitoring of lung disease in mice from neonatal to adult ages.…”
Section: Discussionmentioning
confidence: 54%
“…(AU = arbitrary unit) vessels. For this purpose, 2.5-ml Fenestra-VC (ART Advanced Research Technologies, Saint-Laurent, CA)-a blood pool contrast agent with 50 mg iodine/ml-was injected into the tail vein of the rats, 5 min prior to the data acquisition [1,17]. The mice were given 0.5 ml of the same contrast agent.…”
Section: Animals Contrast Mediamentioning
confidence: 99%
“…It has been reported that doses of more than 5 Gy could be considered as lethal in mice [20,21]. It is recognized that exposure to repeated radiations during follow-up studies can have biological effects on the animal models and thus can affect the experimental results.…”
Section: Discussionmentioning
confidence: 99%